Kinome expression profiling identifies IKBKE as a predictor of overall survival in clear cell renal cell carcinoma patients - Hildebrandt, Michelle A.T. (Oxford University Press, 2012)
There are 516 known kinases in the human genome. Because of their important role maintaining proper cellular function, they are often misregulated during tumorigenesis and associated with clinical outcomes in cancer patients, including clear cell renal cell carcinoma (ccRCC). However, less is known about the global expression status of these genes in renal cell carcinoma and their association with clinical outcomes. We performed a systematic analysis of gene expression for 503 kinases in 93 tumor samples and adjacent normal tissues. Expression patterns for 41 kinases were able to clearly differentiate tumor and normal samples. Expression of I-kappa-B kinase epsilon (IKBKE) was associated with a 5.3-fold increased risk of dying [95% confidence interval (CI): 1.93–14.59, P-value: 0.0012]. Individuals with high IKBKE expression were at a significantly increased risk of death (hazard ratio: 3.34, 95% CI: 1.07–10.40, P-value: 0.038) resulting in a significantly reduced overall survival time compared with those with low IKBKE tumor expression (P-value: 0.049). These results for IKBKE were validated in a replication population consisting of 237 ccRCC patients (P-value: 0.0021). Furthermore, IKBKE was observed to be higher expressed in tumors compared with adjacent normal tissues (P-value < 10(−7)). IKBKE is a member of the nuclear factor-kappaB (NF-κB) signaling pathway and interestingly, gene expression patterns for other members of the NF-κB pathway were not associated with survival, suggesting that IKBKE gene expression may be an independent marker of variation in overall survival. Overall, these results support a novel role for IKBKE expression in modulating overall survival in ccRCC patients.